Toward a Contemporary Definition of Health. (21st November 2018) - Bradley, Kent L; Goetz, Thomas; Viswanathan, Sheila
Abstract: Aristotle saw that the striving of humanity was toward being well – a physical, mental and spiritual state where life flourished. A contemporary definition of health recognizes that disease and disability can and often do co-exist with wellness. In this new conception, health is transformed from a state that requires the absence of disease to a state where the central theme is the fullness of life. Health becomes not a static state of being, but a dynamic quality of living where body, mind, and spirit are fully employed to make the most of each day.